Which effective virtual reality (VR) interventions exist for the prevention and rehabilitation of intimate partner violence (IPV)? - Bastardas-Albero, Adriana; Vall, Berta; Pérez-Testor, Carles; Losilla, Josep-Maria (Frontiers in Virtual Reality, 2023)
Purpose. Prevention and rehabilitation of intimate partner violence (IPV) is a very important topic due to its high prevalence, visibility, and potential to generate negative consequences in survivor's physical and mental health. Previous interventions have used traditional, explicit approaches giving mixed results for both prevention and rehabilitation. However, the number of implicit interventions using technological innovations, specifically virtual reality (VR), is limited in this field. In this review, we aim to find the existing literature on immersive VR targeting prevention or rehabilitation of IPV. Method. The search used several databases: PsycINFO by EBSCOHost, and Medline by PubMed, specifically set to find IPV intervention articles, published after 2010, that included VR in their intervention. Results. 11 studies met all of the eligibility criteria and were included in the review. Conclusion. VR has overall proven useful to tackle the prevention and rehabilitation of intimate partner violence, as it offers the unique possibility of experiencing a variety of situations from a different perspective, in a safe and controlled environment. Therefore, it is a tool which has great potential for transformation, as it allows for experiential and implicit learning.